2022
DOI: 10.18844/cjes.v17i6.7494
|View full text |Cite
|
Sign up to set email alerts
|

Computational thinking in mathematics education: A systematic review

Abstract: As a research area, computational thinking (CT) has gotten increased attention in mathematics education in the last decade. A study identifying patterns in CT research would be essential in understanding the technique for developing CT in mathematics and guiding future research attempts. As a result, the goal of this systematic literature review is to look at the learning methods promoting CT in mathematics lessons. The Preferred Reporting Items for Systematic Review and Meta-Analyses standards were utilised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Even so, the use of technology has proven to be very effective in efforts to develop CT (Bell, 2021;Ruthmann et al, 2010;Scott & Barlowe, 2016). The results of the study showed that the learning approach that is widely used in the integration of CT in learning mathematics is programming based learning (Subramaniam, 2022). These results are in line with research findings that showed the same trend, namely in the five countries that the use of a programming approach in integrating CT in mathematics learning.…”
Section: Discussionsupporting
confidence: 79%
“…Even so, the use of technology has proven to be very effective in efforts to develop CT (Bell, 2021;Ruthmann et al, 2010;Scott & Barlowe, 2016). The results of the study showed that the learning approach that is widely used in the integration of CT in learning mathematics is programming based learning (Subramaniam, 2022). These results are in line with research findings that showed the same trend, namely in the five countries that the use of a programming approach in integrating CT in mathematics learning.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it may aid the upcoming mathematics researchers and educators in planning future studies by assisting them in understanding research patterns in this field. This is in line with [45], who emphasized that publishing trends are a crucial signal for identifying a field's development. Furthermore, the stakeholders, non-government, and government parties, such as mathematics educators and experts or curriculum developers, can now understand the necessities of arranging the forum or seminar with hands-on activity dealing with SEM statistical tools, instead of conducting SEM methodological class virtually for upcoming mathematics scholars.…”
Section: Introductionsupporting
confidence: 85%
“…Both variables aid the students in their attempts to comprehend and master the subjects presented, particularly mathematics. Subramaniam et al ( 2022 ) explained that the subject of mathematics is often considered to be a difficult and boring subject. This has indirectly reduced the students' motivation and interest in learning mathematics.…”
Section: Discussionmentioning
confidence: 99%